Effects of Selective Dorsal Rhizotomy on Ankle Joint Function in Patients With Cerebral Palsy - Filiz Ates; Joline E. Brandenburg; Joline E. Brandenburg; Joline E. Brandenburg; Kenton R. Kaufman (Frontiers Media S.A., 2020)
Selective dorsal rhizotomy (SDR) is a neurosurgical technique performed to reduce muscle spasticity and improve motor functions in children with cerebral palsy (CP). In long term, muscle contractures were observed even after SDR. To better understand what is contributing to contracture formation, it is necessary to assess the effects of SDR on joint stiffness. We hypothesized that ankle passive range of motion (ROM) increases and the quasi-stiffness of the ankle joint decreases after SDR in children with CP. This retrospective study included 10 children with diplegic CP (median age 6 years 2 months) who had undergone SDR and for whom gait analysis data were collected 3 months before (Pre-SDR) and 13 months after (Post-SDR) surgery. Additional to clinical measures, ankle quasi-stiffness (the slope of the ankle moment vs. ankle angle plot) was analyzed from gait data. Passive ankle ROM at 0° (p < 0.0001) and 90° knee angles (p < 0.0001) increased after SDR. Dynamic EMG analysis showed improved phasic gastrocnemius activity (p < 0.0001). Equinus gait was improved with the reduction of peak plantar flexion (p < 0.0001), as well as an increase in peak dorsiflexion (p = 0.006) during walking was observed. Ankle joint quasi-stiffness (Pre- and post-SDR median = 0.056 Nm/kg/° and 0.051 Nm/kg/°, and interquartile range: 0.031 Nm/kg/° and 0.019 Nm/kg/°, respectively) decreased significantly (p = 0.0017) after SDR. Moreover, even though the total time of the gait cycle did not change (p = 0.99), the time interval from maximum dorsiflexion to maximum plantar flexion (Pre- and post-SDR median = 0.125 s and 0.156 s, and interquartile range: 0.153 and 0.253 s, respectively) increased significantly (p = 0.0068) after SDR. In conclusion, the decreased ankle quasi-stiffness and the enhanced time interval in the gait cycle due to SDR indicate better motor control and joint stability. Our findings suggest that the long-term contracture formation occurring even after surgical interventions may be related to the stiffening of non-contractile structures.